Selection of lexical material in the development of the terminology of oil and gas dictionary - Smagulova, Aigerim; Tussupova, Alma (International relations and international law Journal, 2018)
The modern level of development of science and technology is characterized by an enormous amount of information. Even a popular presentation of the latest scientific and technological achievements requires a modern man to have a fairly large amount of terminological vocabulary. Therefore, the study of individual subsections in terminology is being given more and more attention at present. The oil industry is a rapidly developing the branch of the economy. Providing transportation with fuel is an urgent problem for many countries. Drilling is one of the most important branches of the oil and gas production industry, on the level of development of which oil extraction depends to a large extent, especially in hard-to-reach areas of the globe. In the latest achievements of Kazakhstan’s oil and gas industry and the formation of appropriate infrastructure in the region, the successful development of the oil and gas resources of the Caspian Basin of Western Kazakhstan largely depends on the operational use of domestic and foreign achievements by scientists, engineers, economists, oil workers in such areas as well drilling, oil production, the construction of oil pipelines, etc. Terminology as a special branch in the structure of terminology has applied not been fully formed to date. The subject of applied terminology is the comparison of individual terms and their collections related to a certain area of knowledge or activity. In addition, the dependence of the term on terminology and the thermo-system makes it possible to reveal regularities when comparing the content and formal structure of terms belonging to one national language, but belonging to different sets. The basic principles of selection of lexical material and terminology of oil and gas industry is described in this article. In view of the proposed principles of selection was made a brief glossary of the minimum dictionary «Petroleum Engineering». The dictionary includes the terminological vocabulary and some lexical items related to general academic vocabulary.